The Obstructive Sleep Apnea Physical Exam: A Systematic Review and Meta‐Analysis - Nihal Punjabi; Roy W. Qu; Alexandra Vacaru; Brianna Pandey; Shanalee Tamares; Jared C. Inman (Laryngoscope Investigative Otolaryngology, 2025)
ABSTRACT Introduction This systematic review aimed to determine the clinical utility of various physical exam findings in the diagnosis of obstructive sleep apnea (OSA). Methods A systematic review of English articles identified from PubMed, Embase, CENTRAL, and Web of Science databases. Search terms included “sleep apnea,” “physical exam,” “polysomnography,” and all relevant synonyms. Two reviewers independently screened abstracts, reviewed full texts, and extracted data from all studies that presented associations between physical characteristics and apnea‐hypopnea index (AHI). Results A total of 35 studies representing 13,854 patients were included in this review. The mean difference between high AHI and low AHI groups was 4.09 kg/m2 (95% CI: 2.78–5.39) for BMI, 7.93 cm (3.59–12.28) for waist circumference, and 3.67 cm (2.64–4.71) for neck circumference. The odds ratios for having a high AHI were 2.44 (1.07–5.55) for macroglossia, 2.23 (1.68–2.96) for Mallampati > 2, 1.88 (1.67–2.11) for tonsil grade > 2, 3.99 (1.94–8.21) for pharyngeal grade > 2, and 1.57 (1.48–1.67) for enlarged uvula. Thyromental distance, retrognathia, Friedman grade, septal deviation, and enlarged turbinates were also assessed and were not found to be statistically significant between AHI groups. Discussion Several physical exams have strong evidence in the literature supporting their strength at differentiating patients with and without OSA. These should be used routinely among providers who treat OSA, regardless of specialty, to help guide decisions about recommending a sleep study and selecting appropriate treatment. Other physical characteristics may be better assessed through advanced exam techniques or require more research and standardization in the way they are assessed by practitioners.